2014
DOI: 10.1590/s0100-39842014000100012
|View full text |Cite
|
Sign up to set email alerts
|

Sonography of the iliotibial band: spectrum of findings

Abstract: ResumoIliotibial band lesions constitute a potential source of discomfort and are frequently confounded with other conditions which cause pain on the lateral aspect of the hip, thigh and knee. Ultrasonography is usually regarded as a first-line imaging modality in the assessment of such conditions because of its excellent diagnostic accuracy, low cost and wide availability. The correct identification of the structure involved in the production of symptoms leads to an appropriate management and to a higher prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Imaging methods are essential for the evaluation of knee injuries ( 16 , 17 ) . Among the various methods, MRI is one of considerable importance.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging methods are essential for the evaluation of knee injuries ( 16 , 17 ) . Among the various methods, MRI is one of considerable importance.…”
Section: Discussionmentioning
confidence: 99%
“…ITBS is the most common presentation of ITB disease [10]. It is most commonly an overuse injury in runners, arising from the chronic compression of the ITB over a thin, richly innervated layer of fat, positioned between the ITB and the lateral femoral epicondyle [10].…”
Section: Discussionmentioning
confidence: 99%
“…ITBS is the most common presentation of ITB disease [10]. It is most commonly an overuse injury in runners, arising from the chronic compression of the ITB over a thin, richly innervated layer of fat, positioned between the ITB and the lateral femoral epicondyle [10]. Due to its diagnostic accuracy, wide availability, and affordability, USG is quickly becoming the first-line imaging modality in the assessment of ITBS [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Many studies have demonstrated the involvement of the anterolateral ligament (ALL) in rotational stability of the knee. 2 Musculoskeletal injuries include strains, sprains, and iliotibial band syndrome, which account for 47% of all injuries. Severe lower extremity injuries are of particular concern in the active population, accounting for 50% to 75% of all runner injuries and 35% of all musculoskeletal injuries in military personnel.…”
Section: Introductionmentioning
confidence: 99%